ASSESSING WHETHER THERE IS A CANCER PREMIUM FOR THE VALUE OF A STATISTICAL LIFE. (21st March 2013) - Viscusi, W. Kip; Huber, Joel; Bell, Jason
ABSTRACT This article estimates whether there is a cancer risk premium for the value of a statistical life using stated preference valuations of cancer risks for a large, nationally representative US sample. The present value of an expected cancer case that occurs after a one decade latency period is $10.85m, consistent with a cancer premium that is 21% greater than the median value of a statistical life estimates for acute fatalities. This cancer premium is smaller than the premium proposed for policy analyses in the UK and the USA. There is also a greater premium for policies that reduce cancer risks to zero and for risk reductions affecting those who perceive themselves to have a greater than average probability of having cancer. Copyright © 2013 John Wiley & Sons, Ltd.